2017
DOI: 10.1021/acs.jpca.7b04066
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Photosensitized Reactions with Secondary Organic Aerosol Particles in the Presence of Volatile Organic Compounds

Abstract: The ability of a complex mixture of organic compounds found in secondary organic aerosol (SOA) to act as a photosensitizer in the oxidation of volatile organic compounds (VOCs) was investigated. Different types of SOAs were produced in a smog chamber by oxidation of various biogenic and anthropogenic VOCs. The SOA particles were collected from the chamber onto an inert substrate, and the resulting material was exposed to 365 nm radiation in an air flow containing ∼200 ppbv of limonene vapor. The mixing ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…First, different matrices could quench the electronic excitation in the chromophores to a different extent. Another possibility is that photodegradation of BrC chromophores could be not due to direct photolysis but rather occurring through condensed-phase photosensitized reactions (Malecha and Nizkorodov, 2017;Monge et al, 2012), in which case the rate of decomposition would depend on concentration of photosensitizers in the samples as well as viscosity of the material (Hinks et al, 2016;Kaur et al, 2019). Lastly, other absorbing species, such as black carbon, could be shielding BrC chromophores from irradiation, altering the amount of radiation absorbed by BrC chromophores.…”
Section: Aging By Condensed-phase Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…First, different matrices could quench the electronic excitation in the chromophores to a different extent. Another possibility is that photodegradation of BrC chromophores could be not due to direct photolysis but rather occurring through condensed-phase photosensitized reactions (Malecha and Nizkorodov, 2017;Monge et al, 2012), in which case the rate of decomposition would depend on concentration of photosensitizers in the samples as well as viscosity of the material (Hinks et al, 2016;Kaur et al, 2019). Lastly, other absorbing species, such as black carbon, could be shielding BrC chromophores from irradiation, altering the amount of radiation absorbed by BrC chromophores.…”
Section: Aging By Condensed-phase Photochemistrymentioning
confidence: 99%
“…Using infrared spectroscopy they observed the emergence of carboxylic acid, aldehyde, and ketone functionalities during photolysis. Miller and Olejnik (2001) irradiated aqueous solutions of PAH mixtures with UVC lamps. They found that the photodegradation of benzo[a]pyrene and chrysene proceeds more rapidly at acidic pH values and proposed a mechanism based on their findings.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that photodegradation of BrC chromophores could be not direct but rather occurring through condensed-phase photosensitized reactions (Malecha and Nizkorodov, 2017;Monge et al, 2012), in which case the rate of decomposition would depend on concentration of photosensitizers in the samples as well as viscosity of the material (Hinks et al, 2016;Kaur et al, 2019). Lastly, other absorbing species, such as black carbon could be shielding BrC chromophores from irradiation, altering the amount of radiation absorbed by BrC chromophores.…”
Section: Aging By Condensed-phase Photolysismentioning
confidence: 99%
“…BrC, which is excited by visible and ultraviolet radiation in the sunlight, can act as photosensitizer to facilitate free radical reactions and contribute to photochemical aging of organic aerosol (Smith et al, 2014;Yu et al, 2014). The photosensitized uptake of limonene was also observed for several SOA materials containing a complex mixture of photosensitive organic compounds collected from the chamber (Malecha and Nizkorodov, 2017). When aerosols containing photosensitizers such as IC and HA were exposed to isoprene, limonene, α-pinene, β-pinene and toluene in the presence of UV light, there was significant SOA formation (Palacios et al, 2016).…”
Section: Atmospheric Implicationmentioning
confidence: 93%